The Advancement to the Circular Economy. Where We Are and What We Can Do at Local/Regional Level - Angela ALBU (USV Annals of Economics and Public Administration, 2023)
The unsustainable consumption of materials, short lifetimes, and polluting production systems are among the main causes of the critical situation in which we are currently. We need not only a change of behaviour but the change of the old paradigm in which extraction, production, consumption, and disposal were the pillars of the economy with a new paradigm, updated to the reality, in which almost nothing should arrive at the disposal step. The processes must be re-designed to ensure continuous recycling and recovery of useful materials reducing the pressure on the virgin raw materials and eliminating a lot of pollutants specific to the production, use, and disposal steps. The solution seems to be the Circular economy, a concept that is easy to understand but difficult to implement for numerous products and processes. This paper investigates the economic environment of Suceava County to identify the premises for the creation of cycles specific to the circular economy based on the actual industrial profile of the county. The implementation of such cycles can represent best practice models for other counties or for other industrial branches.